Programa novo futuro: entre a legitimidade e a necessidade do ensino médio em tempo integral - Rodrigues, Renato Ribeiro (2016)
The High School is constituted today for brazilian education the last formal school stage of Basic Education. How right training for mid-level for youth in recent decades their senses and/or historical and social meanings are being re-discussed, especially given the number of adjustments and/or political and educational reforms arising from financing conditionality arising from international organizations for the structure, organization and functioning of the entire education system. Considering this, a historical-political-social path that comprises the totality of relations and contradictions derived from the links between capital and labor in education, we seek to develop a reflection on the possibility of offering a High School in Full-Time to unveil and overcome dualities still exist between theory and practice, content and form, manual and intellectual work, human and professional training. To this end, based on the epistemological and theoretical framework of historical and dialectical materialism, we propose the analysis of the Programa Novo Futuro, the State Department of Education, Culture and Sport of Goiás, trying to understand it, and from it, identify elements that allow us to rethink secondary education in addition to meeting the requirements of current economic and production system, considering the importance of the extension of time, space and learning in the acquisition of knowledge and other relationships established in educational practices and/or schooling processes mediated teaching. To do this, we set the following questions: what is the concept of High School in Full-Time in constitutive Programa Novo Futuro, as we give the relationship between the curriculum organization and the process of teaching and learning present in teaching this place and educational foundations can contribute to improving the quality of education, teaching and public school considering the possibility of a High School in Full-Time emancipatory purposes. Thus, we conducted a study by one of the teaching units that materialize the proposal - the Centro de Ensino em Tempo Integral Pedro Xavier Teixeira - and in this place, using as methodological procedures document analysis of the proposal of the Programa Novo Futuro and political-pedagogical project of the school, articulated even the semi-structured interviews with ten subjects belonging to staff (among teachers (as), pedagogical coordination and direction). The information and the responses were grouped into categories of analysis: Public Policy and Educational - Times, Spaces and Learning Extended – High School in Full-Time - and to reconsider the limits and / or possibilities of the Programa Novo Futuro, articulate all this discussion to need for an essentially omnilateral and polytechnic training for youth, from understanding a marxist and gramscian concept in education. Finally, to understand experimentalism and discontinuities of public policies and national educational, regional and local atentamo us to the urgent need for a High School in FullTime that promotes changes in the reconstruction of society, considering the links between human and professional training, education , school and education, capital and labor.